JENIS-JENIS BAKTERI GRAM POSITIF POTENSIAL PATOGEN PADA IKAN BANDENG (CHANOS CHANOS) DI TAMBAK DESA TANJUNG REJO PALUH PUTRI PERCUT SEI TUAN - Jamaluddin Jamaluddin; Dwi Suryanto; Indra Lesmana (AQUACOASTMARINE, 2016)
One of Indonesian popular fish is bandeng (Chanos chanos). One of theproblem facing in bandeng culture is pests and diseases. The purpose of this study wasto observed potential gram-positive bacteria that infects Bandeng fish. The study wasconducted from February to April 2016 in the Laboratory SKIPM Class 1 Medan 1.Samples were taken from infected fish and ponds located in Tanjung Rejo Paluh PutriPercut Sei Tuan. Isolation and characterization of potential bacterial pathogens inBandeng fish was conducted using a scratch plate method. Two bacterial isolates werefound. Identification of the two isolated showed that the isolates were Staphylococcusaureus and Streptococcus iniae.Keywords : Chanos chanos, floating net cages, bacterial pathogens